A Hierarchical Optimization Method for the Design of Active Hybrid Structures - Marker, Paul; Bleicher, Achim (Frontiers in Built Environment, 2022)
In structural engineering, active structures that combine the principles of lightweight construction with bending elastic component behavior are increasingly being investigated. For the realization of a prototype of an active hybrid roof structure at the lab of Hybrid Structures at BTU Cottbus - Senftenberg, preliminary investigations on a case study are conducted in the framework of this publication in order to improve the design process of these type of structures. These active hybrids require a higher design effort compared to classical structures from the field of structural engineering, due to a larger number of relevant objectives. Consequently, this study devotes special attention to these essential target criteria and their mathematical formulation. Furthermore, in order to improve the efficiency of this design process, a hierarchical method is derived, that is subdivided in two successive partial procedures which contain specific heuristics that are developed. In this method, after a structural optimization, an optimal actuator placement is performed. The subject of a design process involving optimal actuator placement is relatively unexplored for active structures in which components are subjected to large elastic bending deformations and is therefore the focus of this study. In order to verify the functionality of the method and the plausibility of the results of the derived partial methods, a validation of the methodology is performed. Therefore results of analyses of an active truss structure are compared with that of an active hybrid structure, both derived using the presented method. In addition to validating results, the study intends to investigate whether the performance of an active hybrid structure generated by the proposed method is sufficiently competitive compared to a state of the art active truss structure derived by the same procedure.